We have emotions but can’t show them! Authoritarian leadership, emotion suppression climate, and team performance - Chiang, Jack Ting-Ju; Chen, Xiao-Ping; Liu, Haiyang; Akutsu, Satoshi; Wang, Zheng (Human relations (New York), 2021)
How do authoritarian leaders in modern organizations influence work team emotional climate and performance? Defining authoritarian leadership as an ambient, demanding, and controlling leadership style, we conducted a survey study of 252 leaders and 765 subordinates matched in 227 work teams in three large public Japanese organizations. The results indicate that authoritarian leaders are more likely to create a team climate of emotion suppression, which induces a higher level of team emotional exhaustion that negatively impacts team performance. Furthermore, we found that authoritarian leaders’ own emotion suppression enhances the above sequential mediation effects, i.e. the more emotion suppression the authoritarian leader him/herself exercises, the stronger the team climate of emotion suppression, the higher the level of team emotional exhaustion, and the lower the team performance. These findings suggest that leadership effectiveness may be improved if leaders can reduce their authoritarian behaviors and identify appropriate channels for employees to release emotions in the workplace.